STINGing the Tumor Microenvironment to Promote Therapeutic Tertiary Lymphoid Structure Development - Filderman, Jessica N.; Appleman, Mark; Chelvanambi, Manoj; Taylor, Jennifer L.; Storkus, Walter J. (Frontiers in Immunology, 2021)
Tertiary lymphoid structures (TLS), also known as ectopic lymphoid structures (ELS) or tertiary lymphoid organs (TLO), represent a unique subset of lymphoid tissues noted for their architectural similarity to lymph nodes, but which conditionally form in peripheral tissues in a milieu of sustained inflammation. TLS serve as regional sites for induction and expansion of the host B and T cell repertoires via an operational paradigm involving mature dendritic cells (DC) and specialized endothelial cells (i.e. high endothelial venules; HEV) in a process directed by TLS-associated cytokines and chemokines. Recent clinical correlations have been reported for the presence of TLS within tumor biopsies with overall patient survival and responsiveness to interventional immunotherapy. Hence, therapeutic strategies to conditionally reinforce TLS formation within the tumor microenvironment (TME) via the targeting of DC, vascular endothelial cells (VEC) and local cytokine/chemokine profiles are actively being developed and tested in translational tumor models and early phase clinical trials. In this regard, a subset of agents that promote tumor vascular normalization (VN) have been observed to coordinately support the development of a pro-inflammatory TME, maturation of DC and VEC, local production of TLS-inducing cytokines and chemokines, and therapeutic TLS formation. This mini-review will focus on STING agonists, which were originally developed as anti-angiogenic agents, but which have recently been shown to be effective in promoting VN and TLS-formation within the therapeutic TME. Future application of these drugs in combination immunotherapy approaches for greater therapeutic efficacy is further discussed.